Soil Organic Matter Impacts on Sugarcane Production on Florida Mineral Soils - Mabry McCray; Stewart Swanson (EDIS)
Sugarcane growth on mineral soils in Florida can often be highly variable as related to the nature of the soils. The soil factor that best relates to sugarcane growth is soil organic matter content. Very stunted sugarcane is also associated with high nematode populations, which indicate high risk of crop damage. This new 4-page publication of the UF/IFAS Agronomy Department discusses grower options for evaluating and increasing soil organic matter. Written by J. Mabry McCray and Stewart Swanson. https://edis.ifas.ufl.edu/ag441